Post Project Environmental Monitoring and Impact Assessment - A Case of Gokarna Sanitary Landfill Site after Operation and Closure - Khanal, Sudarshan Chandra (Scientific World, 2010)
Environmental Assessment (EA) is the identification, prediction and evaluation of Environmental impacts. Environmental Monitoring transforms EA from a one time pre-project document to a continual assessment of impacts. Post project analysis concerns life cycle environmental management and environmental studies during project implementation. This study illustrates significance of Post project Environmental Monitoring and Impact Assessment using a factual example of Gokarna Sanitary Landfill Site (GLFS) after final operation and closure. The environmental inventory, the preventive and compensatory measures adopted by GLFS were studied and some modes of public involvement, economic measures and regulatory measures were analyzed during the construction and operation of the GLFS. Environmental inventory of the site indicated that GLFS might constitute concrete environmental conflict. The result of handpicking analysis showed that risk of medical and industrial hazardous waste cannot be excluded. Water and leachate analysis indicated that the impact of disposal is still pronounced at the site and ground water pollution may be dispersing to the general ground water flow direction. Soil analysis indicated that impact of disposal is pronounced on similar trends in two sites in landfill site. PH, BOD and COD values of leachate indicated that a good biodegradation of organic wastes (i.e. stable methane process) is going on the site and opens a potential for using landfill gas as an energy resource. The public participation, and economic measures studied through questionnaire method confirmed that during operation phase there was inadequate compliance with the planning and operational strategies at implementation that is also a major issue environmentally. There were no provisions for monitoring hazardous wastes, surface and ground water pollution and landfill gas during the operation phase. This study intends to conclude for regular Environmental Monitoring and Post project Impact Assessment for corrective actions and also for the construction and successful operation of similar projects. Possibility of Post project Environmental Monitoring and Impact Assessment in environmental policy making is also considered. Key words: Environmental monitoring; Environmental assessment; Post project analysis; Impact assessment; GLFS. DOI: 10.3126/sw.v5i5.2658 Scientific World, Vol. 5, No. 5, July 2007 60-66